Five-year follow-up of fundus autofluorescence and retinal sensitivity in the fellow eye in exudative age-related macular degeneration in Japan - Shinojima, Ari (PLoS One, 2020)
PURPOSE: To assess the 5-year change in abnormal fundus autofluorescence (FAF) patterns and retinal sensitivity in the fellow eye of Japanese patients with unilateral exudative age-related macular degeneration (AMD). METHODS: Patients with unilateral exudative AMD who developed abnormal FAF in the fellow eyes were enrolled. FAF imaging and microperimetry were performed at baseline and follow-ups. FAF findings were classified into 8 patterns based on the International Fundus Autofluorescence Classification Group to assess retinal sensitivity. Forty-five points covering the central 12 degrees on microperimetry were superimposed onto the FAF images. Each point was classified depending on the distance from the abnormal FAF. “Close” was defined as the portion within 1 degree from the border of any abnormal FAF, and “Distant” was defined as the portion over 1 degree from the border of abnormal FAF. To investigate the association between the retinal sensitivity and distance from the abnormal FAF, hierarchical linear mixed-effect models were used with the distance, time and time squared from baseline (months), and angle (degrees) as fixed effects. Differences among patients, eyes, and test point locations were considered successively nested random effects. RESULTS: We studied 66 fellow eyes with abnormal FAF. Twenty-seven eyes were followed-up during the 5 years. In the 13 of 27 eyes (48%), the abnormal FAF patterns had changed during the 5 years. We found retinal sensitivity was associated significantly with the distance from the abnormal FAF (“Distant”: p<0.001, time(2) from baseline: p<0.001, angle: p<0.001). The mean retinal sensitivity of the “Close” tended to deteriorate after the third year and eventually showed the similar sensitivity as the portion within the abnormal FAF. CONCLUSION: FAF patterns can change about half during the 5 years and the retinal sensitivity near abnormal FAF tends to deteriorate after the third year.